Pendampingan Pengenalan Bahasa Inggris Sejak Dini dengan Belajar sambil Bermain melalui Bimbingan “English For Child” bagi Guru-Guru Raudhatul Athfal dan PAUD - Merry Prima Dewi; Ummil Fatzah; Zatiti Zatiti (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2021)
The community service entitled Introduction to English from an early age by learning while playing through the guidance of"English for Child" is motivated by various problems indicating that children's language skills have not developed optimally, children are more silent, communicate less with their friends, many children cannot socialize and interact with others. environment. Children prefer to play alone rather than playing together with their friends, even in doing group assignments, children cannot do it together orwork together with their friends. the importance of language in human life, and the importance of English to be understood as the language of instruction in the international world, it is necessary to fostermotivation children'sto learn English from an early age withlearning fun. The importance of language in human life, and the importance of English to be understood as the language of instruction in the international world, it isnecessary to foster children's motivation to learn English from an early age withfun learning. The methodology in this study is in the form of research-based service with a participatory reporting approach. While the results of the service carried out can have an impact on Raudhatulteachers Athfal and PAUDso that they can applyway of teaching English